Characterization of metamaterial based patch antenna for worldwide interoperability for microwave access application - Pandharinath R. Satarkar; Rajesh Basant Lohani (Bulletin of Electrical Engineering and Informatics, 2022)
Electromagnetic metamaterial is an artificial material that is made up of different types of structural designs on dielectric substrates. In this paper a broad and elite investigation is being carried out by designing and simulating a metamaterial cell comprising a square split ring resonator with a copper wire strip etched on the ground plane to discover its some unusual parameters such as double negativity of cell which are naturally not found in other materials of nature. A course of action of these unit cells in a grouping shapes metamaterial. These metamaterial cells show exceptionally great applications in the design of microstrip patch antennas by improving their characteristics such as bandwidth, return loss, and gain. The proposed microstrip line feed patch antenna is designed at a 3.5 GHz resonance frequency useful for various worldwide interoperability for microwave access (WiMAX) applications. The ground plane of a substrate of a patch antenna is loaded with a square split-ring resonator, the proposed antenna is fabricated to obtain experimental parameters. A conventional and proposed patch antenna is simulated, fabricated tested analysed, and reported for performance comparison of its parameters.